Circulating Levels of Human Fibroblast Growth Factor 21 are Associated with LDL in Patients with Coronary Artery Disease - Dr. Thoalffakar A. Alhamed; Ayat Shanshol Al-Yasssiry (Journal of Science in Medicine and Life, 2025)
Background: An enzyme called "HFGF21" promotes the hepatocytes' degradation of the low-density lipoprotein receptor (LDL-R). HFGF21 inhibition has emerged as a new target for lipid-lowering medication. Three different types of monocytes are essential to the pathophysiology of atherosclerosis. The purpose of this study was to ascertain if circulating levels of HFGF21 and LDL-liped subgroups are related. Supplies and Methods: We gathered seventy people with coronary artery disease for our study. Levels of HFGF21, LDL liped, and 30 control health were measured. Results: Eighty percent of the cases involved men, whose ages varied from 40 to 70. Compared to 30 male controls, patients had greater levels of HFGF21. In patients, CM was associated with circulating levels of HFGF21, but NCM was inversely correlated with these levels. Individuals whose levels of HFGF21 above the median had a noticeably higher Conclusions: Changes in lifestyle are substantially associated with elevated serum FGF21 levels. smoking, eating a diet high in calories from fat and carbohydrates, taking amino acids, The study shows that risk factors like smoking, high blood pressure, diabetes, obesity, and physical inactivity are strongly correlated with the diagnostic catheterization procedure.